A Comparative Study of Randu Honey Antimicrobial Activity from Several Regions in Java - Nindya Pramesti Wardani; Riesta Primaharinastiti; Achmad Toto Poernomo; Alfi Khatib (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: Randu honey is monofloral honey sourced from a type of plant nectar. The geographical location of randu (Ceiba pentandra) as the source of nectar is one factor that influences the antimicrobial activity of random honey. This research used randu honey from several regions in Java such as Sidoarjo (RSH), Pusat Perlebahan Nasional Bogor (RBH), Kediri (RKH), and Malang (RMH). Objective: To compare the antimicrobial activity of several random honeys (RSH,RBH,RKH, and RMH) against Gram-negative Escherichia coli ATCC 25922, Gram-positive Staphylococcus aureus ATCC 6538, methicillin-resistant Staphylococcus aureus (MRSA) ATCC 33592, and Candida albicans ATCC 10231. Methods: This study used well diffusion and dilution antimicrobial test methods. The diameter of the inhibition zone formed by the well diffusion method was measured using a Vernier caliper. The diffusion method was used as a screening test before determining the quantitative minimum inhibitory concentration (MIC) using serial dilution at a ratio1 of 2 (v/v). Streptomycin and Ketoconazole were used as positive controls. Nutrient broth and Sabouraud broth were incubated at 37°C for 24 h (antibacterial tests) and 25°C for 48 h (antifungal test), respectively. Results: The well diffusion test revealed that all random honey samples could inhibit the test bacteria and fungi with the appearance of an inhibition zone. Diameter inhibition zone ranged from 14.66±0.52 mm to 27.86±0.43 mm. The MICs of RSH,RBH,RKH, and RMH ranged from 3.12% to 25% against all test bacteria and fungi. Conclusion: The results of this study showed randu honey from Bogor (RBH) has the highest antimicrobial activity based on diffusion and dilution tests.